(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes the role of ethics in Imom Bukhari’s teachings in the context of societal development. The main focus is on his work “Al-Adab al-Mufrad,” which highlights ethical values and their impact on social stability and the importance of ethical behavior. The article also explores the relevance of Imom Bukhari’s teachings in contemporary society.